Effect of fungicides and bioagents on number of microorganisms in soil and yield of soybean (Glycine max) - GAURAV MISHRA; NARENDRA KUMAR; KRISHNA GIRI; SHAILESH PANDEY; RAJESH KUMAR (Smujo International, 2014)
Abstract. Mishra G, Kumar N, Giri K, Pandey S, Kumar R. 2014. Effect of fungicides and bioagents on number of microorganisms in soil and yield of soybean (Glycine max). Nusantara Bioscience 6: 45-48. In field experiments, the effect of selected fungicides and bioagents on number of soil microorganisms and yield of soybean (Glycine max L. Merill) was investigated. The results showed that some of the crop protections preparations applied in the experiment (as seed dressing) increased the populations of the examined microorganisms after the harvest of crops. Maximum counts of bacteria were recorded with Thiamethoxam at 3 g kg-1 while Pseudomonas at 3 g kg-1 showed the highest population of fungi, Actinomycetes, Bradyrhizobium japonicum, PSB and Pseudomonas. The highest straw and grain yields of 3241.6 and 1439.4 kg ha-1, respectively, were recorded with Pseudomonas at 3 g kg-1.